Correlation of urethral ratio and bladder wall thickness with cystoscopic findings in posterior urethral valve patients to assess residual valves - Tanmay Motiwala; Arvind Sinha; Kirtikumar J Rathod; Vivek Manchanda; Taruna Yadav; Avinash Jadhav; Manish Pathak; Rahul Saxena (Wolters Kluwer Medknow Publications, 2022)
Introduction: Posterior urethral valve (PUV) is life threatening congenital anomaly of urinary tract. Aim of the study was to correlate urethral ratio (UR) and bladder wall thickness (BWT) with cystoscopic findings in PUV patients to assess residual valves and to validate UR as a diagnostic tool for residual valves. It also aimed to assess the utility of bladder wall thickness in diagnosis of residual valves. Materials and Methods: A total of 31 patients were included in the prospective study done from 2017 to 2019. Calculation of UR was done in oblique VCUG films by dividing maximum posterior and anterior urethral diameter without the catheter insitu. Measurement of BWT was done at dome and bladder neck at full distension with feeding tube insitu and was done at same volume in follow up. The procedure was repeated at 3 months follow up. The findings were compared with cystoscopic findings for the status of residual valves as gold standard. Each patient served as control for self in the study. Results: Median age of presentation was 1 years with range of 1day to 10 years. The most common complains at the time of presentation in our study was straining (35.48%) followed by antenatally diagnosed patients (25.81%) and recurrent UTI (19.36%). Pre fulguration median UR was 2.45. Post Fulguration median UR was 1.20. It showed a statistically significant reduction (p < 0.001) after fulguration. Pre fulguration median BWT was 4 mm. Post fulguration median BWT was 2.5 mm. BWT showed a statistically significant reduction (p < 0.001) after fulguration as well. ROC curve was plotted for UR and BWT. BWT more than 1.95 mm (sensitivity-80%) and UR more than 1.2 (sensitivity-70%) indicates residual valves. Conclusion: A step ladder approach including BWT, UR and check cystoscopy can serve as a new diagnostic algorithm for the assessment of residual valves thereby avoiding extra radiation and general anesthesia exposure.